2016
DOI: 10.1371/journal.pone.0159912
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Fibroblasts Stimulate the Motility of Pancreatic Cancer Cells through IGF1/IGF1R Signaling under Hypoxia

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by its hypovascularity, with an extremely poor prognosis because of its highly invasive nature. PDAC proliferates with abundant stromal cells, suggesting that its invasive activity might be controlled by intercellular interactions between cancer cells and fibroblasts. Using four PDAC cell lines and two pancreas cancer-associated fibroblasts (CAFs), the expression of insulin-like growth factor-1 (IGF1) and IGF1 receptor (IGF1R) was evaluated by RT-PCR, FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 48 publications
(49 reference statements)
3
45
0
Order By: Relevance
“…IGF1 is a cancer progression-related gene that is associated with the growth, metastasis and chemoresistance of various cancers (23)(24)(25)(26)(27). In the present study, we confirmed that TAMs significantly expressed higher IGF1 levels than M0 cells as (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…IGF1 is a cancer progression-related gene that is associated with the growth, metastasis and chemoresistance of various cancers (23)(24)(25)(26)(27). In the present study, we confirmed that TAMs significantly expressed higher IGF1 levels than M0 cells as (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…This pathway can enhance the proliferation and development of cells by initiating the anti-apoptotic PI3K/Akt/mTOR and the mitogenic Ras/Raf/Mek/Erk pathways (21,22). The IGF1 pathway is associated with the growth, metastasis and clinical outcome of various cancers, including prostate cancer, gastric cancer, lung cancer and breast cancer (23)(24)(25)(26)(27). For example, CAFs can increase the invasion ability of pancreatic cancer cells via paracrine IGF1/ IGF1R signaling, particularly under hypoxia (27), and IGF1R is highly expressed in chronic lymphocytic leukemia cells, whereas the inhibition of IGF1R can enhance the death of CLL cells (28).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, tumor cells stabilize HIF-1α in CAFs by increasing ROS production to increase glycolysis, leading to the formation of a “pseudohypoxic” environment for CAFs 97 . In addition, Hirakawa et al 98 demonstrated that the motility of PCCs cocultured with CAFs was greater under hypoxic conditions than under normoxic conditions, partly via paracrine IGF1/IGF1R signaling.…”
Section: Cafs and Tumor Metabolism In Pdacmentioning
confidence: 99%
“…In addition to Shh, stromal (myo-) fibroblasts can also become activated under tumor hypoxia. Indeed, PDACs are hypovascularized and thus hypoxic tumors [ 34 ]. In PDAC, cancer-associated fibroblasts produce IGF-1 under hypoxic conditions and promote tumor cell migration via IGF-1R signaling under hypoxia in vitro [ 34 ].…”
Section: Introductionmentioning
confidence: 99%